2022
DOI: 10.1186/s12936-022-04230-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the residual efficacy and physical durability of five long-lasting insecticidal nets (LLINs) in Senegal

Abstract: Background The preventive and curative strategies of malaria are based on promoting the use of long-lasting insecticidal nets (LLINs) and treating confirmed cases with artemisinin-based combination therapy. These strategies have led to a sharp decline in the burden of malaria, which remains a significant public health problem in sub-Saharan countries. The objective of this study was to determine and compare the residual efficacy of LLINs recommended by the World Health Organization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The current proliferation of several LLIN brands in the market, although aimed at providing affordable LLINs owing to an increased demand, need to be subjected to appropriate and stringent checks to sieve out lower quality LLINs [ 46 ]. Data on LLIN durability under field conditions, that are provided by qualified testing laboratories, should serve to determine LLINs’ functional life and actual impact; they should also be used by the manufacturers to improve the quality of nets produced [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current proliferation of several LLIN brands in the market, although aimed at providing affordable LLINs owing to an increased demand, need to be subjected to appropriate and stringent checks to sieve out lower quality LLINs [ 46 ]. Data on LLIN durability under field conditions, that are provided by qualified testing laboratories, should serve to determine LLINs’ functional life and actual impact; they should also be used by the manufacturers to improve the quality of nets produced [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ITN control method relies on pyrethroids, besides that a study conducted by Diouf in Senegal reported that the lack of effectiveness of using mosquito nets in controlling malaria is related to the washing of mosquito nets and patterns of good net conditions such as restless children's sleeping behavior, the size of mosquito nets that too small for a bed and conducive to stretching. 31 Evaluation and development of mosquito vector control carried out in ve regions in sub-Saharan Africa, namely by using multiple ITNs with ITN dual-AI types relative to standards, pyrethroids are only ITNs that still provide protection from malaria, especially when access and use are high. 32 While the IRS method is non-pyretorid and is effectively used for scale endemic areas considering that the insecticide will last a long time and the costs required are very economical.…”
Section: Discussionmentioning
confidence: 99%